The Challenge of Model A School Principal’s Performance Evaluation Using Comprehensive E-Penjelas Software - Zulkifli, Zulkifli; Putri, Febrina Riska; Jaenam, Jaenam; Yulastri, Weni; Asril, Asril; Azwar, Azwar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
The focus of this research is on the process of understanding comprehensive e-penjelas software as an application for evaluating the performance of school principals. This study analyzes lawsuits comprehensively using e-penjelas characteristics, namely the assessment team's characteristics, the assessment's scope, the stages of assessment, and the characteristics of the principal's performance appraisal application. This study used a quantitative approach using a Likert scale questionnaire which was distributed to the performance appraisal team for school principals in Padang City Middle School, West Sumatra Province, Indonesia, including school supervisors, school committees, MKKS (Principal Work Meeting), school principals, teachers, staffing and elements of students totaling 66 respondents. Data analysis was carried out through a descriptive statistical approach. The results of the characteristic study stated that the assessment team, the scope of the assessment, the stages of the assessment, and the characteristics of the school principal's performance assessment application in the comprehensive e-penjelas software were by user expectations in the excellent category with an ability score of 77.98%. The comprehensive use of e-penjelas software as an assessment platform for school principal performance requires infrastructure support through policy support and adequate internet access.